Carbohydrate paste ingestion during prolonged treadmill running - Hotell, M. D.; Faria, I. E. (Medicine & Science in Sports & Exercise, 1996)
Trained endurance runners (N = 10) completed two 2-hour treadmill runs at 70% VO2max in a fasted state one week apart. One run used 25 gm dissolved in 200 ml of water taken every 30 minutes. The other followed the same regimen but used a placebo. The CHO supplemented trial maintained an elevated blood glucose level during the two hour trial while in the placebo trial, there was a gradual decline. Implication. Ingesting 25 gm of glucose paste with water every half hour will maintain blood glucose levels in moderately hard steady-state work.